ACARORUM CATALOGUS VIII. Trombidiformes, Prostigmata, Superfamilia Cheyletoidea (Cheyletidae, Psorergatidae, Demodecidae, Harpyrhynchidae, Syringophilidae), Superfamilia Cloacaroidea (Cloacaridae, Epimyodicidae) - Beron, Peter (Pensoft Series Faunistica, 2021)
The eight volume of this series "Acarorum Catalogus" is devoted to Superfamilia Cheyletoidea (Cheyletidae, Psorergatidae, Demodecidae, Harpyrhynchidae, Syringophilidae) and Superfamilia Cloacaroidea (Cloacaridae, Epimyodicidae). About 1243 species of 177 genera are listed therein, with synonymies and citations in various papers. The book also contains a list of by-country distributions, type localities, hosts of the parasitic species, and lists of authors who published on any known species of these families. There are lists of publications for each of the families. The last two volumes of the same series on the patterns of the first eight are underway.